2015
DOI: 10.1007/s10865-015-9634-5
|View full text |Cite
|
Sign up to set email alerts
|

Field experiment of a very brief worksite intervention to improve nutrition among health care workers

Abstract: Despite the potential of worksite interventions to boost productivity and save insurance costs, they tend to be costly and tested in nonrandomized trials. The aim of the present study was to test the ability of a very brief worksite intervention based on implementation intentions to improve nutrition among health care workers. Seventy-nine health care workers were randomly allocated to a control condition or to form implementation intentions using standard instructions or with a supporting tool. Fruit intake a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Fourth, a no-treatment control was not used therefore it is not possible to determine if the effects on physical activity are due to increases in the intervention condition or decreases in the control condition. There are two lines of evidence that the effect shown in this study is genuine: (a) previous studies that have compared standard volitional help sheets, active control and no-treatment have found null effects between the no-treatment and the active control (Armitage, 2008;) and (b) further studies have found no detrimental effects of the active control condition across a range of behaviors (Arden & Armitage, 2010;Armitage, 2008;Armitage, 2015;.…”
Section: Limitationssupporting
confidence: 50%
See 3 more Smart Citations
“…Fourth, a no-treatment control was not used therefore it is not possible to determine if the effects on physical activity are due to increases in the intervention condition or decreases in the control condition. There are two lines of evidence that the effect shown in this study is genuine: (a) previous studies that have compared standard volitional help sheets, active control and no-treatment have found null effects between the no-treatment and the active control (Armitage, 2008;) and (b) further studies have found no detrimental effects of the active control condition across a range of behaviors (Arden & Armitage, 2010;Armitage, 2008;Armitage, 2015;.…”
Section: Limitationssupporting
confidence: 50%
“…The effectiveness of the two versions of the physical activity volitional help sheet contribute to an emerging body of evidence that the volitional help sheet is a useful means of bringing about behavior change Armitage, 2015;Armitage, 2008;Armitage & Arden, 2010;Brewster et al, 2015). This study also builds on previous research by Armitage and Arden (2010) who found that the volitional help sheet was effective in increasing moderate physical activity in manual workers over one month.…”
Section: Effects On Physical Activitymentioning
confidence: 60%
See 2 more Smart Citations
“…The volitional help sheet has been tested in randomized controlled studies in several domains including smoking (Armitage 2008 , 2016 ), alcohol consumption (Armitage and Arden 2012 ), self-harm (Armitage et al 2016 ), dietary intake (Armitage 2015 ), and physical activity (Armitage and Arden 2010 ), but only once in the domain of weight loss. Armitage et al ( 2014 ) randomly allocated 72 overweight participants who were participating in a commercial weight-loss program in the UK to either an intervention (volitional help sheet) condition or a control (distracter task) condition.…”
Section: Volitional Help Sheetsmentioning
confidence: 99%